153 Effects of dietay copper on production and hatching performance of Chinese Yellow broiler breeder hens during egg-laying period. (7th December 2018) - Gou, Z; Fan, Q; Li, L; Wang, Y; Lin, X; Zheng, C; Jiang, S
Abstract: The objective of this study is to investigate the effects of dietary copper (Cu) levels on production and hatching performance of Chinese Yellow broiler breeder hens during egg-laying period. A total of 576 birds were allotted into 6 treatments, each of which consisted of 6 replicates (8 cages for each replicate with 2 birds per cage). The basal diet contained 3.71 mg/kg Cu (control), and the other 5 treatment diets additionally supplemented with 5, 10, 20, 40 and 80 mg/kg Cu into the basal diet respectively. The study lasted for 15 weeks including 3 week of adaptation and depletion of the stored Cu in body. Production and hatiching performacne of breeder hens were determined. The results demonstrated that there were no significant differences of laying rate, egg weight and daily egg mass of breeder hens fed different dietary Cu (P > 0.05). The qualified egg rate (excluding those with double-yolk, soft-shell, cracked, very small malformed, etc.) was affected by dietary Cu (P < 0.01). The qualified egg rates of 3.71, 8.71 and 13.71 mg/kg Cu groups were all greater than those of 23.71 and 83.71 mg/kg Cu groups respectively (P < 0.05). Moreover, the rate of qualified eggs for hatching (52 to 60 g with nomal egg shape) of 13.71 mg/kg Cu group was the greatest and higher than that of 3.71, 23.71 and 83.71 mg/kg Cu groups respectively (P < 0.05). Fertility rate and hatchability were not affected by dietary Cu level (P > 0.05). The proportion of live embryos that hatched of 13.71 mg/kg Cu group was the greatest and greater than that of 8.71, 43.71 and 83.71 mg/kg Cu groups respectively (P < 0.05). It was concluded that excess dietary Cu can influence egg quality and survival of embryos. The optimal dietary Cu of Chinese Yellow broiler breeders during egg-laying period is 13.71 mg/kg.